A case study of farming in Australia's high rainfall zone: exploring past and future potential farming intensification and biodiversity management. Issue 1 (2nd January 2016) - Carr-Cornish, Simone; Hall, Nina
Abstract : This case study explored the intentions of farmers to intensify their farming in Australia's high rainfall zone (HRZ). The zone spans across eastern Australia and small portions of South Australia and south-western Western Australia. The zone supports both high farming productivity and significant biodiversity, and has the potential for future intensification. The research aim was to identify past and future planned changes to farming intensification, the motivations for such changes and the existing approaches for conserving biodiversity. Seventeen farmers were interviewed from across the zone's three regions. These interviews afforded in-depth exploration of intensification from a perspective that was scarce in the literature. The interviews indicated that the majority of farmers had increased cropping over the last five years, whereas both cropping and the grazing of sheep were likely to increase over the next five years. Farmers reflected a strong commitment to biodiversity conservation initiatives, although the ability to carry out these initiatives was reported to be contingent on resources that were constrained during land use change and intensification. Given that such change brings both biodiversity conservation opportunities and threats, these findings can inform agricultural extension and policy that is concerned with the intensification of farming in the HRZ.